La industria académica : la universidad bajo el imperio de la tecnocracia global. Carlos Hoevel, Teseo, Ciudad Autónoma de Buenos Aires, 2021, 368 págs - Dalbosco, Hugo Luis (2022)
Fil: Dalbosco, Hugo Luis. Pontificia Universidad Católica Argentina; Argentina